Karakteristik Penyakit Diabetes Melitus Tipe 2 di Puskesmas Maccini Sawah Makassar Tahun 2023-2024 - Nur Intan; Armanto Makmun (Yayasan Citra Cendekia Celebes, 2025)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by elevated blood sugar levels caused by impaired insulin secretion, insulin action or both. Diabetes mellitus is the sixth ranked cause of death in the world, this was revealed by the World Health Organization (WHO). The International Diabetes Federation (IDF) states that there are around 463 million people aged 20-79 years in the world who have diabetes in 2019 or around 9.3% of the total population of the same age. Based on the health profile in 2019 of South Sulawesi Province, there were 148,311 cases of diabetes mellitus in South Sulawesi. Makassar City occupies the first position of the highest number of cases of diabetes mellitus in South Sulawesi province, namely 27,004 cases. The type of research used is a descriptive and retrospective case study design. The sample used was PRB diabetes mellitus patients at Maccini Sawah Health Center and selected by purposive sampling method from medical records with the most complete data from 2023-2024 and obtained there were 59 patients. The results showed that the majority of patients with type 2 diabetes mellitus were female as many as 40 patients (67.8%) while men were 19 patients (32.2%), the age of diabetes mellitus patients was mostly at the age of 60-69 years around 30 patients (50.8%) and for the most body mass index with the overweight category as many as 25 patients (42.4%).